Secondary hypogonadism after surgical treatment of patients with tumors of the chiasmosellar aria - Ya. A. Kan; M. G. Zhestikova (Бюллетень сибирской медицины)
A frequency of secondary hypogonadism after surgical treatment of patients with tumors of the chiasmosellar aria was defined. 30 patients were examined. A secondary hypogonadism was revealed in 70% of cases. The average levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) both in male in female were lowered or were on the low bound of the norm. This phenomenon denotes to the secondary nature of the hypogonadism. Most often secondary hypogonadism developed in patients operated apropos of the craniopharyngeoma and prolactinoma.